Some Derivative-Free Quadrature Rules for Numerical Approximations of Cauchy Principal Value of Integrals. (17th March 2014) - Das, Rabindranath; Hota, Manoj Kumar; Bej, Manoranjan
Abstract : Some derivative-free six-point quadrature rules for approximate evaluation of Cauchy principal value of integrals have been constructed in this paper. Rules are numerically verified by suitable integrals, their degrees of precision have been determined, and their respective errors have been asymptotically estimated.